Investment Incentives and Electricity Spot Market Design - Veronika Grimm; Gregor Zöttl (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
In liberalized electricity markets strategic firms compete in an environment characterized by fluctuating demand and non-storability of electricity. While spot market design under those conditions by now is well understood, a rigorous analysis of investment incentives is still missing. Existing models, as the peak-load-pricing approach, analyze welfare optimal investment and find that optimal investment is higher with more competitive spot markets. In this article we want to extend the analysis to investment decisions of strategic firms that anticipate competition on many consecutive spot markets with fluctuating (and possibly uncertain) demand. We study how the degree of spot market competition affects investment incentives and welfare and provide an application of the model to electricity market data. Our results show that more competitive spot market prices strictly decrease investment incentives of strategic firms. The reduction of investment incentives can be so intense to even offset the beneficial impact of more competitive spot market design. Those results obtain with and without free entry. Our analysis thus demonstrates that investment incentives necessarily have to be taken into account for a meaningful assessment of proper electricity spot market design.
urn:nbn:de:bvb:19-epub-11705-4
Keywords: D43; L13; D41; D42; D81; 330; Investment; demand fluctuation; cost fluctuation; spot market design; Strompreis; Spotmarkt; Warenbörse; Mechanismus-Design-Theorie; Wettbewerb; Elektrizitätswirtschaft; Investition; Ökonomischer Anreiz; Theorie